2018
DOI: 10.1111/ejn.14268
|View full text |Cite
|
Sign up to set email alerts
|

Circadian pacemaker neurons of the Madeira cockroach are inhibited and activated by GABAA and GABAB receptors

Abstract: GABA is the most abundant neurotransmitter in the circadian pacemaker circuits of mammals and insects. In the Madeira cockroach the accessory medulla (AME) in the brain′s optic lobes is the circadian clock that orchestrates rest‐activity rhythms in synchrony with light dark cycles. Three prominent GABAergic tracts connect the AME to termination sites of compound eye photoreceptors in the lamina and medulla. Parallel GABAergic light entrainment pathways were suggested to either advance or delay the clock for ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 48 publications
1
8
0
Order By: Relevance
“…More recent work has shown specifically that the accessory medulla of the optic lobe is critical for nocturnal behavior such that electrical recordings from this region show rapid increases in electrical activity more frequently at night (Schneider & Stengl, ). Neurophysiological activity of clock neurons in these invertebrates is inhibited or excited by GABA (see Giese, Wei, & Stengl, in this Special Issue) similar to results reported in vertebrate clocks, where GABA is involved in entrainment and synchronization (Albers, Walton, Gamble, McNeill, & Hummer, ). Invertebrate electrical rhythms may be important for learning given that these cockroaches are better at olfactory learning and recall during the night phase compared to during the day (Decker, McConnaughey, & Page, ).…”
Section: Electrical Rhythms In Invertebrate Speciessupporting
confidence: 76%
“…More recent work has shown specifically that the accessory medulla of the optic lobe is critical for nocturnal behavior such that electrical recordings from this region show rapid increases in electrical activity more frequently at night (Schneider & Stengl, ). Neurophysiological activity of clock neurons in these invertebrates is inhibited or excited by GABA (see Giese, Wei, & Stengl, in this Special Issue) similar to results reported in vertebrate clocks, where GABA is involved in entrainment and synchronization (Albers, Walton, Gamble, McNeill, & Hummer, ). Invertebrate electrical rhythms may be important for learning given that these cockroaches are better at olfactory learning and recall during the night phase compared to during the day (Decker, McConnaughey, & Page, ).…”
Section: Electrical Rhythms In Invertebrate Speciessupporting
confidence: 76%
“…However, we found dose‐dependent calcium increases in L1/L2 after GABA bath application. Several studies have reported excitatory GABA effects, both in mammals and in insects, either via chloride‐gradient‐dependent GABAa receptors or metabotropic GABAb receptors (Giese, Wei, & Stengl, 2018; Haam et al., 2012; Kobayashi, Matsuo, Sadamoto, Watanabe, & Ito, 2012). Hardie (1987) demonstrated acetylcholine could depolarize the lamina monopolar neurons in houseflies.…”
Section: Discussionmentioning
confidence: 99%
“…GABAa receptors or metabotropic GABAb receptors (Giese, Wei, & Stengl, 2018;Haam et al, 2012;Kobayashi, Matsuo, Sadamoto, Watanabe, & Ito, 2012). Hardie (1987) demonstrated acetylcholine could depolarize the lamina monopolar neurons in houseflies.…”
Section: Lawf1 Neurons Inhibit Activities In L1/l2 Neurons Through mentioning
confidence: 99%
“…In cockroaches, circadian neurons have been found to exert both inhibitory and excitatory responses to GABA, depending on the balance of NKCC1 / KCC2 activity. About 50% of all cockroach clock neurons respond to GABA, and about 30% of all GABA-responsive neurons show an increase of [Ca 2+ ] i as GABA response, which was correlated with enhanced NKCC expression compared to KCC 15 . In the mammalian brain clock, the suprachiasmatic nucleus (SCN), expression and activity of the two opposing cotransporters NKCC1 and KCC2 underlie daily and regional variation.…”
Section: Discussionmentioning
confidence: 92%